(untitled) (The Planet, 2024)
Introduction: Hemoglobin E (HbE) hemoglobinopathy is one of the most prevalent inherited hemoglobin disorders in Southeast Asia, including Bangladesh. Elevated hemoglobin A2 (HbA2) levels serve as an important diagnostic marker for distinguishing HbE-related conditions. This study aimed to analyze the composition of HbA2 in individuals with HbE hemoglobinopathy using capillary electrophoresis. Methods & Materials: A cross-sectional study was conducted on 50 participants clinically diagnosed with HbE hemoglobinopathy. Hemoglobin analysis was performed using the Sebia Capillarys 2 system. Data on HbA2 levels, anemia severity, and hemoglobinopathy subtypes were analyzed, and statistical significance was determined at p<0.05. Results: Elevated HbA2 levels were observed in 68% of participants, while 28% had normal levels, and 4% had below-normal levels (p=0.02). Mild anemia was the most prevalent (64%), followed by moderate (20%) and severe anemia (16%). Gender analysis revealed that moderate anemia was exclusive to females, while severe anemia was predominantly observed in males. HbE trait was the most common hemoglobinopathy type (84%), with HbE disease and HbE/β-thalassemia comprising 14% and 2%, respectively. Hemoglobin indices indicated microcytic and hypochromic anemia across the study population. Conclusion: Capillary electrophoresis is a robust diagnostic tool for quantifying HbA2 levels and characterizing HbE hemoglobinopathy. The high prevalence of elevated HbA2 highlights its significance in differentiating hemoglobinopathy subtypes, providing valuable insights for clinical management and screening programs in resource-limited settings.